Handmaid : The Power Of Names In Theology And Society - Mbonu, Caroline (Wipf And Stock Publishers, 2010)
A project of women's advancement in society and church life engages a multi disciplinary and interdisplinary approach in its quest for social transformation.The discussions on these pages seek to contribute to the women's discourse with insights from theology and culture;more specifically designation.
Keywords: Non Fiction; Theology; Women